#TITLE_ALTERNATIVE# - AMMARULLAH (NIM : 25112004), ALI
Land cover change is one of the things that greatly affect the global climate change to the living environment of living beings. West Java Province is one of the provinces in Indonesia which has the dynamics of change in land use is high. The high socio-economic activities in this area will have an impact on land cover change. Factors that influence land cover changes such as physical, social and economic development factors in West Java has not been studied well so it is necessary to study about the factors that influence the land cover changes in West Java and how these factors affect land cover change. Land cover changes, in a certain location and in a certain period of time, can be studied as a phenomenon or event that is dichotomous. Binary logistic regression (BLR) is a regression model where the response variable is binary or dichotomous. Binary logistic regression model could predict whether the driving factors such as slope, bentuk lereng, height, distance to the main roads, the distance to the provincial capital, the number of population, distance to the settlement, and the central business district (CBD) has effect on changes in land cover. These results indicate that if we do binary logistic regression analysis partialy, all predictor variables that are used have significant effect with different properties on the probability of changes in land cover. Meanwhile, if we do overall regression analysis, the variable bentuk lereng has no significant effect on the probability of changes in land cover in West Java.